(untitled) (Research, Society and Development, 2021)
The present study aimed to perform the phytochemical analysis and evaluate the sun protection factor (SPF) of the aqueous extract of the fruit peels of Tamarindus indica L. (Tamarindo). The phytochemical profile was determined through the methodology used by Matos (1997); the FPS in vitro through the methodology of Mansur et al. (1986) by performing scans with the aid of a spectrophotometer (290 to 320nm) with 5nm intervals in concentrations of (50, 100, 500 and 1000 μg / mL) of the aqueous extract of Tamarindus indica L. The results obtained showed that concentrations of 50 and 500μg.mL-1 showed the photoprotective potential with SPF of 6.54 and 12.77, respectively. Based on these data, I can conclude that the aqueous extract from the peels of the Tamarindus indica L. fruit is a promising natural product for possible use as a sunscreen, considering that it has alkaloids and tannins as secondary metabolites, molecules with good biological potential.